2014
DOI: 10.4103/1117-6806.137310
|View full text |Cite
|
Sign up to set email alerts
|

Wound complications following laparoscopic surgery in a Nigerian Hospital

Abstract: Background:Different complications may occur at laparoscopic port sites. The incidence of these varies with the size of the ports and the types of procedure performed through them.Objectives:The aim was to observe the rate and types of complications attending laparoscopic port wounds and to identify risk factors for their occurrence.Patients and Methods:This is a prospective descriptive study of all patients who had laparoscopic operations in one general surgery unit of a University Teaching Hospital in Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…All cases of superficial PSI were successfully managed by standard wound care and antibiotics. Similar results were also reported by Karthik et al [5] and Adisha et al [3] Interestingly, all cases of deep PSI were reported typically from 4 th to 8 th week of the surgery. Majority of these cases had a grade III deep PSI (57.14%) followed by grade IV (21.42%) and grade II (14.28%) PSI as per chaudhuri et al classification [10] .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…All cases of superficial PSI were successfully managed by standard wound care and antibiotics. Similar results were also reported by Karthik et al [5] and Adisha et al [3] Interestingly, all cases of deep PSI were reported typically from 4 th to 8 th week of the surgery. Majority of these cases had a grade III deep PSI (57.14%) followed by grade IV (21.42%) and grade II (14.28%) PSI as per chaudhuri et al classification [10] .…”
Section: Resultssupporting
confidence: 90%
“…Laparoscopic surgery has become the order of the day due to its time-tested vantages over conventional open surgery; better cosmesis, less pain, faster convalescence and early return to work are the few of the rewards which appeal to the masses resulting in their overwhelming espousal over the past few decades. [1][2][3] Even in developing countries like India, there is a recent surge in pursuing the art of laparoscopy among all surgical specialities both in private and public hospitals with a substantially hike with the advancing time. Laparoscopic cholecystectomy has literally supplanted open cholecystectomy as the "gold standard" procedure for symptomatic gallstone disease.…”
Section: Introductionmentioning
confidence: 99%
“…15 In various reports the rate of incidence varies and amounts to around 4%. 7,8,12,[16][17][18] However, PSI emerged as the most common complication in our study at an incidence of 63.5%. All of these cases were identified in the late post-operative period with maximum cases noted in between 3-4 weeks post-surgery.…”
Section: Discussionmentioning
confidence: 84%
“…These complications are relatively lesser and reported in only a few studies. As far as hypertrophic scar is concerned, among different studies reviewed by us, only one study (Adisa et al, 2014) [29] had mentioned it as a complication in their series.…”
Section: Discussionmentioning
confidence: 99%
“…Karthik et al, 2013; Adisa et al, 2014 [29] mentioned about oncologic surgery and reported of a single case of port site metastasis. On reviewing the literature, we found the mention of port site metastasis among exclusive series of oncologic laparoscopic surgeries to be ranging from 0% to 16%.…”
Section: Discussionmentioning
confidence: 99%